The Role of Thrombosis and Vessel Injury in Acute Myocardial Infarction: Current Standard of Care and Therapeutic Options - Vargas, Ian; Wickline, Samuel A; Pan, Hua (Cardiology and Cardiovascular Medicine, 2021)
Despite recent advances in therapy, acute myocardial infarction (AMI) remains a major cause of morbidity and mortality. Among the most significant pathologic mechanisms contributing to AMI are vessel injury and thrombosis, which are prime targets for therapies in the clinical setting. Endothelial dysfunction precedes atherosclerotic plaque rupture and/or erosion, which promote platelet plug formation and the activation of the coagulation cascade and thrombin that leads to coronary occlusion. In current clinical practice, two general strategies have been developed for treating this acute, initial presenting event: mechanical and pharmacologic intervention. The former involves physical disruption of the clot through percutaneous coronary intervention (PCI), while the latter involves administration of various thrombolytic and anticlotting agents. Prior clinical trials have solidified primary PCI and stenting as the definitive method of treatment of AMI. Unfortunately, primary PCI is limited by relatively low availability, which has prompted the study of alternative forms of PCI and pharmacologic therapy such as fibrinolysis. However, many patients fail to achieve adequate revascularization and suffer various morbidities in the days to weeks following AMI. To this end, recent studies have examined adjunctive interventions aimed at inducing vessel and myocardial repair such as angiogenic factors and stem cell injections, among others. This review will describe the landscape of thrombosis and vessel injury in AMI, from current clinical practice for targeting these mechanisms to more recent studies advancing basic knowledge in the field.